Desenvolvimento profissional de professores iniciantes : narrativas de experiências no contexto da escola pública - Aimi, Deusodete Rita da Silva (2019)
This thesis is the result of a research carried out in the line of research School Organization, Training and Pedagogical Practices of the Post-Graduation Program in Education of the Federal University of Mato Grosso and it has as its central theme the learning experiences of beginner educators in the context of public schools. The research involved three public schools, together with four participants, who were teachers egressed from the course of pedagogy of the Federal University of Mato Grosso that began their work after passing a public service exam and hired permanently as teachers of the initial years in the municipality of Cuiabá/MT. It has as main objective: to understand, through narratives, how beginner teachers produce meanings, appropriating and sharing meanings about the experiences of teaching. This investigation was based on the theoretical assumptions of narrative research. The period of construction of narratives in the context of teachers' work began in March 2017 and ended in December 2018. For the composition of the field texts, which taken together make up the narrative of each participant, it was used: narrative interview; memorial built in the undergraduate course, informal conversations, texts and audios produced and sent from the platform WhatsApp and other texts produced by teachers, such as: texts published in blog, logbook and field notes of the researcher. Concerning the construction of the field texts and, consequently, the research text, its organization was thought from the methodological guidelines considering three aspects related to the narrative research method: 1) theoretical considerations; 2) practical considerations and oriented to the field text; e) 3 analytic-interpretative considerations, at the time of transition of field texts. The composition of the meanings built with the participants was organized in two thematic axes: Tensions experienced in the context of the school, systematized from the themes: physical space, loneliness and other feelings; hostile environment; indiscipline; lack of support and monitoring and difficulties when working with students target public of the special education; and learning meant in the process of professional development, organized based on the following themes: initial training; training needs; planning; construction of pedagogical knowledge of content; reflection; forms of record; development of autonomy and investment in professional development itself. The analyses highlighted a continuous and challenging complex process of becoming a teacher in the context of the public school, dialoguing with the formative issues, still recent, in the transition between ceasing to be Pedagogy students to become teachers. The research allowed, above all, seeing closely the tensions and learnings experienced by them, showing that the beginner teacher has much to say about his professional development process.